2022
DOI: 10.1038/s41598-022-05366-w
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization agents for fs laser writing in PDMS

Abstract: This study aims at identifying compounds incorporated into Polydimethylsiloxane (PDMS) which produce large refractive index change under fs laser exposition, potentially leading to optimal writing of waveguides or photonic devices in such a soft host. Germanium derivative, titania and zirconite derivatives, benzophenone (Bp), irgacure-184/500/1173 and 2959 are investigated. We show a mapping of the RI index change relative to the writing speed (1 to 40 mm/s), the repetition rate (606 to 101 kHz) and the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…To understand the effect of aging on the studied materials after fs-laser writing, we performed a kinetic study. Our aging measurements were dependent on several writing parameters reported previously by us, such as a power range from 4 to 8 mW, a writing speed of 20 mm·s –1 , a repetition rate in the range of 101–606 kHz, λ writing of 515 nm, a pulse width of 250 fs, number of passes 1–8, and focus lens (NA) of 0.01 and 0.25. These parameters can vary between photoinitiators depending on their chemical sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand the effect of aging on the studied materials after fs-laser writing, we performed a kinetic study. Our aging measurements were dependent on several writing parameters reported previously by us, such as a power range from 4 to 8 mW, a writing speed of 20 mm·s –1 , a repetition rate in the range of 101–606 kHz, λ writing of 515 nm, a pulse width of 250 fs, number of passes 1–8, and focus lens (NA) of 0.01 and 0.25. These parameters can vary between photoinitiators depending on their chemical sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a–e, physical characterization of the polymer was performed, and the results revealed that the highest RI change was 15 times larger than the best result obtained with pure PDMS, indicating the successful incorporation of the photoinitiator into the polymer network. A wavelength of λ = 515 nm was used to influence the course of the reaction during the writing, and this influence can be adjusted by changing the writing speed, the number of passes, and the repetition rate, as detailed in our previous report . This enhancement indicates the successful incorporation of the photoinitiators into the polymer network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Taking control over it enables 3D printing inside the volume of the already solidified/dried resins, for example, the is a rapidly increasing interest in writing waveguiding free-form structures and photonic bonds. [18][19][20] However, up to date the controlled cross-linking has only been exploited for bulky shape (volumetric) structures via refractive index modification inside the resin/resist. Thus, it invites to refer to as (3+1)D writing as was named in the original report.…”
Section: Introductionmentioning
confidence: 99%